A full-scale evaluation of the effects of different disinfection methods on the removal of contaminants of emerging concern - Agostina Chiavola; Camilla Di Marcantonio; Serena Lamberti; Alessandro Frugis; Valentina Gioia; Simone Leoni; Massimo Spizzirri (Journal of Water Process Engineering, 2025)

Potential impact of tide-regulation barriers on the formation of methylmercury in the Venice Lagoon (Italy) - Carla Pereira-Garcia; Andrea G. Bravo; Claudia Cosio; Andrea Gallorini; Simone Leoni; Daniele Cassin; Stéphane Guédron; Thierry Adatte; Miguel Cabrera-Brufau; Olga Sánchez; Silvia G. Acinas; David Amouroux; et al. (Journal of Hazardous Materials, 2025)

Standard area diagrams for tomato early blight severity assessments on leaves and leaflets - Breno Benvindo dos Anjos; Victor Côco Lirio; Matheus Ricardo da Rocha; Sophia Machado Ferreira da Silva; Simone de Paiva Caetano Bucker Moraes; Leônidas Leoni Belan; Waldir Cintra de Jesus Junior; Wanderson Bucker Moraes; André da Silva Xavier; Fábio Ramos Alves; Willian Bucker Moraes (Australasian Plant Pathology, 2024)

Eutrophication history and organic carbon burial rate recorded in sediment cores from the Mar Piccolo of Taranto (Italy) - Janusz Dominik; Simone Leoni; Daniele Cassin; Irene Guarneri; Luca Giorgio Bellucci; Roberto Zonta (Environmental Science and Pollution Research, 2023)
During the second half of the twentieth century, coastal lagoons in densely populated regions experienced eutrophication due to excessive nutrient inputs. Detrimental effects, including hypoxia/anoxia and harmful algae blooms, have occurred in many Mediterranean lagoons, but their trophic evolution is poorly documented. The lack of adequate monitoring data can partly be offset by examining sedimentary records. In the Mar Piccolo, a lagoon comprising two basins near Taranto (Italy), eutrophication has followed population growth and pollution resulting from naval activities and massive industrialisation. Based on 210 Pb-dated sediment cores, continuous in situ density profiles obtained with computed tomography, organic carbon (OC) and total nitrogen (TN) content and OC and TN isotopic signatures, this paper reconstructs the history of eutrophication, discusses the sources of organic matter and provides an estimate of the OC burial rate before and during the eutrophic period. OC burial increased in the period 1928–1935 and peaked in the decade 1960–1970. OC and TN content were still high in the surface sediments collected in 2013, despite partial diversion of sewage outfalls in the period 2000–2005. The divergent δ 13 C and δ 15 N signatures of the two basins during the eutrophic period suggest they were affected by different nutrient sources. The OC burial rate during the eutrophic phase (≈ 46 g m −2 y −1 ) was close to the world median value for lagoon sediments, and was about twice the burial rate recorded in the preceding oligotrophic phase.

A step forward on site-specific environmental risk assessment and insight into the main influencing factors of CECs removal from wastewater - Camilla Di Marcantonio; Agostina Chiavola; Valentina Gioia; Simone Leoni; Giancarlo Cecchini; Alessandro Frugis; Claudia Ceci; Massimo Spizzirri; Maria Rosaria Boni (Journal of Environmental Management, 2023)

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

The contribution of Potamogeton crispus to the phosphorus budget of an urban shallow lake: Lake Monger, Western Australia - Barbara Leoni; Clelia Luisa Marti; Elena Forasacco; Matteo Mattavelli; Valentina Soler; Pietro Fumagalli; Jörg Imberger; Simone Rezzonico; Letizia Garibaldi (Limnology, 2016)